The Facebook social network as a teaching resource in the extracurricular educational teaching-learning process of English language of the students of Séptimo Semester Class "A"at Carrera de Idiomas at Universidad Nacional de Chimborazo, city of Riobamba in the academic term March-July 2015 - Iguasnia Guala, Mayra Jacqueline (2016)
The purpose of the research was to study how students use Facebook to further their studies. This research is important because institutions appear to be using social networking to recruit and retain students. Students even use such technology to further their studies or what they believe might be good institutional uses for social media with regard to their academic programs. The application of Facebook social network as a teaching resource in the extracurricular educational teaching-learning process of the English language of the students of Séptimo Semester Class "A"at Carrera de Idiomas at Universidad Nacional de Chimborazo, helped them to improve and reinforce their English language. The present work contains 4 chapters that are developed as follows: Chapter I refers to Referential Framework which provides information about: the topic of the thesis, the problem setting, the problem formulation, and the general and specific objectives.